Assessing the Effectiveness of First Step to Success: Are Short-Term Results the First Step to Long-Term Behavioral Improvements?. (March 2013) - Sumi, W. Carl; Woodbridge, Michelle W.; Javitz, Harold S.; Thornton, S. Patrick; Wagner, Mary; Rouspil, Kristen; Yu, Jennifer W.; Seeley, John R.; Walker, Hill M.; Golly, Annemieke; Small, Jason W.; Feil, Edward G.; et al.
This article reports on the effectiveness of First Step to Success, a secondary-level intervention appropriate for students in early elementary school who experience moderate to severe behavior problems and are at risk for academic failure. The authors demonstrate the intervention's short-term effects on multiple behavioral and academic outcomes as delivered off-the-shelf in a variety of classrooms and schools across the country—effects that were mitigated by fidelity of implementation. Furthermore, the authors assess the body of evidence on First Step to Success against the standards for effectiveness and widespread dissemination promulgated by the Society for Prevention Research, thereby suggesting directions for further research.